A New Buyer-Seller Watermarking Protocol with Discrete Cosine Transform - Kumar, Ashwani; Ansari, Mohd Dilshad; Ali, Jabir; Kumar, Kapil (Computer Networks and Information Technologies, 2011)
Digital water marking is a promising technology to embed information as unperceivable signals in digital contents. Buyer-seller watermarking protocols with Discrete Cosine Transform (DCT) integrate multimedia watermarking and fingerprinting with cryptography, for copyright protection, piracy tracing, and privacy protection. It uses the public key encryption schemes. In this paper we propose a New Buyer Seller water marking protocol with DCT which is secure and flexible and gives more security from previous watermarking protocols to both buyer and seller. In this we use Public Key Infrastructure (PKI), arbitrator and watermarking certificate authority (WCA) for better security.